2018
DOI: 10.26501/jibm/2018.0801-009
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Role of Islamic Work Ethics and Mediating Role of Organizational Identification on Leader-Member Exchange and Citizenship Behavior Relationship: A Test of Moderated Mediation Model

Abstract: The present study aims to investigate the indirect relationship of Leader-Member Exchange (LMX) and followers' citizenship behavior through Organizational Identification (OI) for the first time using Social Identity Theory (STI), and to widen the scope of research by explaining differences in LMX-citizenship behavior relationship through OI arising from a moderating role of Islamic Work Ethics (IWE). The questionnaire comprising supervisor and subordinate-rated measures and a time-lagged data collection design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Javaid et al (2018) suggest that employees who adhere to the principles of IWE have reported positive and productive work ethics within their respective workplaces. Similarly, Hussain et al (2018) also support that the involvement of IWE in an organization could prove to be a healthy practice. Finally, Farid et al (2019) highlight that several empirical studies have reported that IWE is a positive moderator that focuses on the well-being of employees:…”
Section: Moderating Role Of Islamic Work Ethicsmentioning
confidence: 57%
“…Javaid et al (2018) suggest that employees who adhere to the principles of IWE have reported positive and productive work ethics within their respective workplaces. Similarly, Hussain et al (2018) also support that the involvement of IWE in an organization could prove to be a healthy practice. Finally, Farid et al (2019) highlight that several empirical studies have reported that IWE is a positive moderator that focuses on the well-being of employees:…”
Section: Moderating Role Of Islamic Work Ethicsmentioning
confidence: 57%
“…It suggests that work could likewise be righteousness considering an individual's needs, and ought to be a need for setting up balance in one's individual and public activity (Ali, 1992). Islamic working environment morals consider work to be a wellspring of Halal income and individuals who trust Islamic work esteems are more distant to negative practices and more slanted towards pro-social practices (Hussain, Shahzad, Khan, and Ahmad, 2018). Like Allah accentuates in Qur'ān stanzas about the persistence, resilience, and tolerant to foul practices from partners and chiefs (Tufail et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It implies that work is a virtue in light of a person's needs, and is a necessity for establishing equilibrium in one's individual and social life (Ali, 1992). Islamic workplace ethics see work as a source of Halal Income and people who believe in Islamic work values are more tolerant to negative behaviors and more inclined towards pro-social behaviors (Hussain et al, 2018). And have patience with what they say, and leave them with noble (dignity) (Qur'ān 73:10).…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have employed the framework of SIT to explain the mediating role of LMX between benevolent leadership and followers' task performance and OCBs (i.e. Hussain et al, 2018). Therefore, using the broader framework of SIT (Tajfel and Turner, 1985) and LMX literature, this study proposes the following hypothesis.…”
Section: Servant Leadership and Lmxmentioning
confidence: 97%
“…To address such voids, this study considers leader-member-exchange (LMX) as intervening variable that may lead to enhancement of organizational identification and career satisfaction. LMX, a dyadic relationship between a leader and follower (Hussain et al, 2018), is characterized by its relationship orientation. This makes it particularly relevant for the hospitality sector, which is fundamentally a relationship-oriented industry.…”
mentioning
confidence: 99%